Using video analysis for concussion surveillance in Australian football - Makdissi, M.; Davis, G. (Journal of Science and Medicine in Sport, 2016)
Objectives The objectives of the study were to assess the relationship between various player and game factors and risk of concussion; and to assess the reliability of video analysis for mechanistic assessment of concussion in Australian football. Design Prospective cohort study. Methods All impacts and collisions resulting in concussion were identified during the 2011 Australian Football League season. An extensive list of factors for assessment was created based upon previous analysis of concussion in Australian Football League and expert opinions. The authors independently reviewed the video clips and correlation for each factor was examined. Results A total of 82 concussions were reported in 194 games (rate: 8.7 concussions per 1000 match hours; 95% confidence interval: 6.9-10.5). Player demographics and game variables such as venue, timing of the game (day, night or twilight), quarter, travel status (home or interstate) or score margin did not demonstrate a significant relationship with risk of concussion; although a higher percentage of concussions occurred in the first 5 min of game time of the quarter (36.6%), when compared to the last 5 min (20.7%). Variables with good inter-rater agreement included position on the ground, circumstances of the injury and cause of the impact. The remainder of the variables assessed had fair-poor inter-rater agreement. Common problems included insufficient or poor quality video and interpretation issues related to the definitions used. Conclusions Clear definitions and good quality video from multiple camera angles are required to improve the utility of video analysis for concussion surveillance in Australian football.